Locally identified criteria, indicators and verifiers for evaluating sustainable community based forestry: a case from Nepal - Pokharel, R. K.; Tiwari, K. R. (Banko Janakari, 2018)
Community based forestry is seen in many countries as a way to enhance sustainable forest management through close involvement of local people. This paper aims to develop understanding of local perspectives on criteria, indicators and verifiers for evaluating sustainable community based forest management practices. This study includes ten different forest user groups ranging from full autonomy to semi-autonomy in making decisions regarding forest management practices covering three districts from three physiographic (mid-hill, inner-tarai and tarai) regions of Nepal. A village to village approach was used to acquire the perspectives from male, female and different castes. The findings show that local people identified four criteria, 26 indicators and 60 verifiers for evaluating sustainable community based forest management practices. Three locally identified criteria were found to be identical with the institutional topdown criteria. The paper concludes that understanding local knowledge, local practice and associated institutions are important to manage forest resources in a sustainable manner. There is also a need to have continuous collaborative works between forest professionals and local people to enhance sustainable forest management. Banko Janakari A Journal of Forestry Information for Nepal Vol. 28, No. 1, 2018, page: 37-47